2007
DOI: 10.1037/0021-9010.92.6.1625
|View full text |Cite
|
Sign up to set email alerts
|

The relationships among asymmetry in task dependence, perceived helping behavior, and trust.

Abstract: Social relations analyses involving 132 working relationships among 60 individuals from 29 teams revealed that an increase in a team member's task dependence on another team member was associated with higher levels of perceived help from and interpersonal trust in that specific team member, provided the other member was highly task dependent on the focal member. The degree to which an actor perceived a relationship with a partner to be helpful partially mediated the relationship between task dependence and tru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
152
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 136 publications
(165 citation statements)
references
References 74 publications
12
152
0
1
Order By: Relevance
“…Thus, we attempted to provide more than a simple response to scholars' calls for more research on this topic (e.g., Langfred, 2005;Molleman, 2009;Rasmussen & Jeppesen, 2006) by also providing an alternative theoretical perspective that can be used to gain a better understanding of this interaction at a new level of analysis. Our alternative perspective is based on powerdependence theory (Emerson, 1962), interdependence theory (Thibaut & Kelley, 1959), recent reviews of the power literature (e.g., Fiske & Berdahl, 2007), and recent studies on power that focused on asymmetries in task dependence (De Jong et al, 2007;Van der Vegt et al, 2010). Based on these theories and studies, we hypothesized, and subsequently demonstrated, that team members who report they are highly taskinterdependent and highly task autonomous are considered relatively powerful by their peers.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, we attempted to provide more than a simple response to scholars' calls for more research on this topic (e.g., Langfred, 2005;Molleman, 2009;Rasmussen & Jeppesen, 2006) by also providing an alternative theoretical perspective that can be used to gain a better understanding of this interaction at a new level of analysis. Our alternative perspective is based on powerdependence theory (Emerson, 1962), interdependence theory (Thibaut & Kelley, 1959), recent reviews of the power literature (e.g., Fiske & Berdahl, 2007), and recent studies on power that focused on asymmetries in task dependence (De Jong et al, 2007;Van der Vegt et al, 2010). Based on these theories and studies, we hypothesized, and subsequently demonstrated, that team members who report they are highly taskinterdependent and highly task autonomous are considered relatively powerful by their peers.…”
Section: Discussionmentioning
confidence: 99%
“…Molleman, 2009). Based on recent studies focused on power that results from asymmetries in task dependence (De Jong et al, 2007;Van der Vegt et al, 2010), as well as on literature related to power-dependence theory (e.g., Emerson, 1962;Fiske & Berdahl, 2007;Keltner et al, 2003), we argued above that the interaction of task interdependence and task autonomy is related to the power of individual team members. Below, we will argue that, if this is indeed a valid line of reasoning, this interaction should also be related to individual performance because more powerful team members should be in better positions to successfully complete their tasks than their less powerful colleagues.…”
Section: Task Interdependence Task Autonomy and Individual Performancementioning
confidence: 95%
See 3 more Smart Citations